Justification of the Technological Scheme for a Disc Potato Digger with Elastic Fingers - Akbarov Sherzod Botirovich; Meliyeva Dildorakhon Davlatjon qizi; Mukhtarov Boburbek Rakhmonali o‘g‘li (American Journal of Botany and Bioengineering, 2025)
The study revealed a decrease in the efficiency of the sieving process due to uneven distribution of the soil-potato mixture along the sorting elevator in potato harvesters. To address this issue, a design for a sorting elevator with an elastic-fingered disc was proposed. This device evenly distributes the mass across the elevator’s transverse surface, intensifies sieving, and reduces damage to tubers